The role of women in the juxtaposition between Islam and political Islam: unveiling Arabian nights - Rosati, Enrico Matteo (2019)
The resurgence of Islamic Fundamentalism determined a new wave of interest about Muslim countries; Islam became a privileged category of analysis to investigate the commitment of these countries through a democratic path. Women's role in Islam is extremely relevant since the relationship between religion and gender issues has become a fertile ground of discussion in academia, and also in local and transnational politics, in colonial and postcolonial analysis, in the affirmation of economic and political powers, and in the definition of identities. This Master thesis unfolds some pivotal issues to highlight the Quran and the Sunnah’s gender egalitarian attitude. Thus Sharia is enforced on the base of an ahistorical and patriarchal interpretation of the sacred texts. Moreover, there is not only one Political Islam, and women’s living conditions vary notably from country to country, from region to region. This work aims at understanding the miscellany, the variety, the juxtaposition among Islamic morals and legislation in three case studies: Hezbollah, Hamas and the Muslim Brotherhood. Additionally, it tries to overcome several dualities offering an approach to a society founded on the Ethic of Care, on Progressive Islam and Islamic Feminism, on the base that each human being is different from others and that differences enrich us.